Evaluation of mite allergen-induced Th1 and Th2 cytokine secretion of peripheral blood mononuclear cells from atopic dermatitis patients: association between IL-13 and mite-specific IgE levels - Wakugawa, Motoshi; Hayashi, Keiko; Nakamura, Koichiro; Tamaki, Kunihiko (Journal of dermatological science, 2001)
There have been several reports about Th1/Th2 imbalances in atopic dermatitis (AD), but there have been few precise investigations about the differences between Th1 and Th2 cytokine secretion patterns of peripheral blood mononuclear cells (PBMCs) in such patients. We cultured PBMCs, taken from AD patients and healthy subjects, with dust mite extract (DME) and measured subsequent immunoreactive interferon (IFN)-γ (Th1 cytokine), interleukin (IL)-4, IL-5, and IL-13 (Th2 cytokines) levels in the supernatants by ELISA assays. There is a difference between IL-4 and IL-13 secretion patterns by DME-stimulated PBMCs in AD subjects; immunoreactive IL-4 levels were detectable maximally within 24-h cultures, while IL-13 levels increased time-dependently within 7-day cultures. IL-13 levels were significantly elevated in AD subjects compared to healthy subjects, while IFN-γ levels did not significantly differ between the two groups. IL-13 levels were significantly higher in AD patients who had high levels (>100 U/ml) of Dermatophagoides pteronyssinus-specific IgE (Dp-IgE) than in those AD patients who had low levels (<10 U/ml) of Dp-IgE. Tacrolimus (FK-506), at a concentration of 10 −8 M, significantly inhibited DME-induced IL-13 production from PBMCs. These findings suggest that IL-13 produced by Th2 cells are involved in IgE overproduction in AD subjects.